Peran Kepuasan Konsumen sebagai Pemediasi Promosi Sosial Media dan Diskon terhadap Loyalitas Konsumen - Thifal Khairunnisa; Annisa Fajri; Haerudin (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2024)
Generation Z is a potential consumer for e-commerce, because this generation grew up with the internet and uses it every day, Generation Z is very familiar with it and believes that this is a very important medium. So, it is important to create loyal consumers which is the core of every business and for companies loyalty is very important. In this research, we use the role of consumer satisfaction as a mediator of consumer loyalty towards social media promotions and discounts. The object of this research is Management Study Program students at Muhammadiyah University Semarang who have made purchases on Shopee e-commerce at least 3 times. Sampling using incidental sampling is a technique used to determine samples based on anyone who happens to fill out a Google form. The results of this research are that there is a mediating role for consumer satisfaction to increase consumer loyalty through social media promotions and discounts.